1995
DOI: 10.1152/ajpregu.1995.268.1.r156
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic response to vasopressin during V1-receptor antagonism in baroreflex-deficient subjects

Abstract: Six quadriplegic subjects and 6 control subjects received high-dose arginine vasopressin (AVP) infusions at rates of 500, 1,000, 2,000, and 4,000 microU.kg-1.min-1 in consecutive 10-min intervals. Six additional quadriplegic subjects received low-dose AVP infusions at rates of 50, 100, 200, 400, and 800 microU.kg-1.min-1. All subjects were studied once with and once without administration of a selective V1-receptor antagonist. During high-dose AVP infusions without V1-receptor blockade, mean arterial pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…After cervical and upper thoracic SCI, unopposed parasympathetic pathways predominate and worsen hemodynamic control systems both acutely and chronically. The biochemical mechanisms involved include an initial increase followed by a prolonged, chronic decrease in circulating catecholamines, impaired vascular responses to vasopressin, and increased nitric oxide-mediated vasodilation [18,[37][38][39][40]. Chronic changes in alpha-adrenergic receptor sensitivity have also been recognized and, along with other mechanisms, may predispose patients to lifethreatening episodes of autonomic dysreflexia [41,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After cervical and upper thoracic SCI, unopposed parasympathetic pathways predominate and worsen hemodynamic control systems both acutely and chronically. The biochemical mechanisms involved include an initial increase followed by a prolonged, chronic decrease in circulating catecholamines, impaired vascular responses to vasopressin, and increased nitric oxide-mediated vasodilation [18,[37][38][39][40]. Chronic changes in alpha-adrenergic receptor sensitivity have also been recognized and, along with other mechanisms, may predispose patients to lifethreatening episodes of autonomic dysreflexia [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…In individuals with chronic SCI, diurnal variation in serum AVP concentration is attenuated and can lead to nocturnal enuresis, which is effectively treated with exogenous vasopressin [46,47]. The vasoconstrictive actions of AVP are well known; however, AVP also has vasodilatory properties at least in part via activation of vasopressin-2 (V 2 ) receptors, as hypotension has been observed in individuals with chronic quadriplegia after administration of a V 1 receptor antagonist [39,40,48,49]. This study is the first to measure acute changes in serum AVP concentration in response to SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it should be recognized that cholinoceptor and α‐adrenoceptor blockade by atropine and phenoxybenzamine might have interrupted the efferent outflow of central sympathetic inhibition and hence reduced the vasodepressor response. AVP is known to affect baroreflex and inhibit central sympathetic outflow, causing a decrease in heart rate and cardiac output (Cowley et al , 1984; Webb et al , 1986; Shimizu et al , 1993; Huch et al , 1995). Thus, a central action for the hypotensive VP peptides could not be ruled out in our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Regionally, VP can induce vasodilation (Liard, 1988; Naitoh et al , 1993; Nakanishi et al , 1995; Tagawa et al , 1995; van Lieburg et al , 1995). It also enhances the arterial baroreflex, leading to a depression of heart rate and cardiac output (Cowley et al , 1984; Webb et al , 1986; Shimizu et al , 1993; Huch et al , 1995). It is now generally accepted that VP may play an important role in maintaining systemic blood pressure and in regulating regional blood flows during extreme hemodynamic alterations such as in a hypovolemic state (Schwartz & Reid, 1983; Landry et al , 1997; Reid, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanisms involved in the vasodilatory response to AVP are incompletely understood and may not be uniformly the same in all segments of the circulation. Although there is evidence that AVP-induced vasodilation may involve V 1 receptors in some highly localized vascular beds (16,17), a vasodilatory effect of AVP has been most clearly demonstrated following V 1 -receptor antagonist administration (13,20,27,28). In early studies reported by Schwartz and Reid (28), V 1 -receptor antagonist administration in water-deprived conscious dogs was shown to produce hemodynamic changes that were the opposite of those usually associated with increased levels of AVP, i.e., cardiac output (CI), heart rate (HR), and plasma renin activity (PRA) were increased.…”
mentioning
confidence: 99%